Combination of positive charges and honeycomb pores to promote MC3T3-E1 cell behaviour. Issue 53 (11th June 2015) - Zhao, Changhong; Pan, Changjiang; Sandstedt, Joakim; Fu, Yifeng; Lindahl, Anders; Liu, Johan
<x xml:space="preserve">Abstract</x> Symmetric poly(l-lactide) (PLLA)-based dendritic l-lysine copolymer, with the PLLA block as the core and the lysine dendrons in the two ends, was prepared through a divergent method. The honeycomb pores on this copolymer film significantly enhanced the MC3T3-E1 cell functions.